Enceladus Auroral Hiss Emissions During Cassini's Grand Finale. Issue 15 (14th August 2018) - Sulaiman, A. H.; Kurth, W. S.; Hospodarsky, G. B.; Averkamp, T. F.; Ye, S.‐Y.; Menietti, J. D.; Farrell, W. M.; Gurnett, D. A.; Persoon, A. M.; Dougherty, M. K.; Hunt, G. J.
Abstract: Cassini's Radio and Plasma Wave Science (RPWS) instrument detected intense auroral hiss emissions during one of its perikrone passes of the Grand Finale orbits. The emissions were detected when Cassini traversed a flux tube connected to Enceladus' orbit (L‐shell = 4) and at a time when both the spacecraft and the icy moon were in similar longitudes. Previous observations of auroral hiss related to Enceladus were made only during close flybys and here we present the first observation of such emissions close to Saturn. Further, ray‐tracing analysis shows the source location at a latitude of 63°, in excellent agreement with earlier UVIS observations of Enceladus' auroral footprint by Pryor et al. (2011, https://doi.org/10.1038/nature09928 ). The detection has been afforded exclusively by the Grand Finale phase, which enabled sampling of Enceladus' high‐latitude flux tube near Saturn. This result provides new insight into the spatial extent of the electrodynamic interaction between Saturn and Enceladus. Plain Language Summary: Cassini's high‐inclination Grand Finale orbits brought the spacecraft closer to Saturn than ever before, with the closest approach between the cloud tops and the inner edge of the D ring. This unprecedented set of orbits introduced a new view of Saturn's system by enabling direct measurements of high‐latitude Enceladus flux tubes close to Saturn. Here we present evidence of communication between Saturn's ionosphere and Enceladus during the Grand Finale orbits, revealing the vast spatial extent of their coupling via plasma waves. Key Points: Complex whistler mode auroral hiss emissions were detected during the Grand Finale Emissions were detected on the Enceladus flux tube, and for the first time, not local to Enceladus but very close to Saturn Source region is co‐located with previous observations of Enceladus' auroral hot spot